(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to clarify the concept of domain analysis and its importance in knowledge organization. The significance of the study lies in the supportive capabilities of this tool in organizing knowledge and designing its systems. The study was conducted to answer the main question: "How does domain analysis contribute to the organization of knowledge and its systems?" Given the nature of the study topic, the inductive approach was used as the most suitable for achieving its objectives. The study presented several results, including the conclusion that domain analysis is considered a socio-cognitive approach that focuses on understanding the nature of knowledge within social groups and its impact on information provision. Domain analysis is also considered one of the key methods in knowledge organization by identifying the natural arrangements of knowledge in each domain and the best ways to organize recorded knowledge for retrieval purposes. It can also be seen as an activity or methodology for discovering conceptual content and natural or guiding arrangements in specific knowledge domains. The study also provided several recommendations, such as applying domain analysis as a fundamental method in knowledge organization to understand the nature and arrangements of knowledge in various domains, and training knowledge specialists on domain analysis to provide effective and suitable knowledge services for users’ needs. Furthermore, efforts should continue to enhance the performance of domain analysis in knowledge organization using experimental analytical tools and discourse analysis.